A Study of some Integral Equations - Abderrazak, MEHELLOU; Dhia Seif Eddine, LAOUID (My University, 2022)
In this research paper,we have dealt with Solution and application of Singular In- tegral Equations Involving Logarithmically Kernel.This research consists of fort main chapters.The first chapter was about generalities of spaces and operator .The second one covers the Classification ,Existence , Uniqueness and converting of integral equa- tions and the last two chapter tacked solution and application Singular Integral Equa- tions Involving Logarithmically Kernel.Eventually we hope that we succeed in present- ing this thesis throughly and simtly.Dans ce document de recherche, nous avons traité de la solution et de l’application de l’intégrale singulière Équations impliquant un noyau logarithmique.Cette recherche consiste en fort main chapitres. Le premier chapitre portait sur les généralités des es- paces et des opérateurs. Le second on couvre la classification, l’existence, l’unicité et la conversion des équations intégrales et les deux derniers chapitres ont abordé la so- lution et l’application des équations intégrales singulières Impliquant logarithmique- ment le noyau. Nous espérons finalement réussir à présenter cette thèse de manière approfondie et simple.
mémoire master mathématique
Keywords: spaces, operators , Integral Equations, Existence and Uniqueness , Logarithmically Kernel, Water Wave Problem.; espaces, opérateurs, équations intégrales, existence et unicité, Kernel logarithmique, problème d’onde d’eau.